Analisis Profitabilitas Pada Kinerja Keuangan (Studi Kasus pada PT. Jiwasraya (Persero) Regional Office I) - Irvan Yoga Pardistya (UNSIKA (Universitas Singaperbangsa Karawang), 2019)
This study aims to analyze performance of company based on profitability. The data of study is financial report 2009-2012. The methode of study of deecrptive quantitavie when the data is processed to show financial perform with NPM (Net Profit Margin), Return on Asset (ROA) and Return on investment (ROI). The results show NPM, ROA & ROI have been decreased since 2010. Therefore, for the last 3 years company suffered a loss; 1. NPM decreased in 2010-2012 because the number of profits in the company decreased every year, 2. ROA has decreased in 2010-2012 because, the number of profits every year in the company has decreased as well. 3. ROI has decreased in 2010-2012 because, the amount of net income has increased which resulted in investment returns also increasing.